2014
DOI: 10.11591/ijphs.v3i2.4680
|View full text |Cite
|
Sign up to set email alerts
|

Fish Marketing Status with Formalin Treatment in Bangladesh

Abstract: <p>Fish possess an extremely strong cultural attachment considering irreplaceable animal food source in Bangladeshi diet beset with nutritional importance. It has been getting endangered by abominable practice of formalin in marketing leaded by some deceitful traders counting profit beyond ethical attainment and endangering public health. This paper outlines the formalin extremity with a several years practice in fish marketing involving almost 5% city markets with a petty heterogeneity comprising contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 7 publications
0
20
0
2
Order By: Relevance
“…Bangladesh has been suffering from rampant food adulteration for the last few decades which causes numerous deaths along with countless physical illnesses (Ali, 2013a;Goon et al, 2014). At present, illegal use of formalin and other chemicals in foods is considered to be a major public health problem in Bangladesh (Ali, 2013b;Rasul, 2013;Goon et al, 2014) and it has been reported that people are now suffering from 'food phobia' (Rasul, 2013). Vegetables, fruits, sweetmeats, milk, fish, bakery products, puffed rice, cereals, soybean oil, mustard oil, butter oil and other foods are adulterated in different ways with various chemicals (Hossain, 2011;Khan, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bangladesh has been suffering from rampant food adulteration for the last few decades which causes numerous deaths along with countless physical illnesses (Ali, 2013a;Goon et al, 2014). At present, illegal use of formalin and other chemicals in foods is considered to be a major public health problem in Bangladesh (Ali, 2013b;Rasul, 2013;Goon et al, 2014) and it has been reported that people are now suffering from 'food phobia' (Rasul, 2013). Vegetables, fruits, sweetmeats, milk, fish, bakery products, puffed rice, cereals, soybean oil, mustard oil, butter oil and other foods are adulterated in different ways with various chemicals (Hossain, 2011;Khan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables, fruits, sweetmeats, milk, fish, bakery products, puffed rice, cereals, soybean oil, mustard oil, butter oil and other foods are adulterated in different ways with various chemicals (Hossain, 2011;Khan, 2013). A common practice among food vendors is to spray fish, fruits and vegetables with chemical preservatives including formalin to boost their lifespan and appearance (Khan, 2013;Goon et al, 2014). Dishonest businessmen are inventing newer and newer techniques of adulteration, and thus carbide, formalin, textile colours, artificial sweeteners, DDT, urea, and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations